Influenza A Virus Proteins NS1 and Hemagglutinin Along with M2 Are Involved in Stimulation of Autophagy in Infected Cells - Zhirnov, O. P. (American Society for Microbiology, 2013)
The NS1 protein of influenza A virus is known to downregulate apoptosis early in infection in order to support virus replication (O. P. Zhirnov, T. E. Konakova, T. Wolff, and H. D. Klenk, J. Virol. 76:1617–1625, 2002). In the present study, we analyzed the development of autophagy, another mechanism to protect cells from degradation that depends on NS1 expression. To this end, we compared autophagy in cells infected with wild-type (WT) influenza virus and virus lacking the NS1 gene (delNS1 virus). The results show that in WT-infected cells but not in delNS1 virus-infected cells, synthesis of the autophagy marker LC3-II, the lipidated form of microtubule light chain-associated protein LC3, is stimulated and that LC3-II accumulates in a perinuclear zone enriched with double-layered membrane vesicles characteristic of autophagosomes. Transfection experiments revealed that NS1 expressed alone was unable to upregulate autophagy, whereas hemagglutinin (HA) and M2 were. Proteolytic cleavage of HA increased autophagy. Taken together, these observations indicate that NS1 stimulates autophagy indirectly by upregulating the synthesis of HA and M2. Thus, it appears that NS1, besides downregulating apoptosis, is involved in upregulation of autophagy and that it supports the survival of infected cells by both mechanisms.